Design of a New Virtual Interaction Based PLC Training Using Virtual Sensors and Actuators: System and Its Application - Yoon Sang Kim; Hak-Man Kim (International Journal of Distributed Sensor Networks)
This paper proposes a new virtual interaction based programmable logic controller (PLC) training system using virtual sensors and actuators. The proposed system is composed of four components including virtual sensors (for interacting between user and input devices), virtual actuators (for manipulating and controlling device or equipment), virtual PLC (for programming and generating command), and virtual networks (for interfacing the interactions and transferring the data between all the components). The proposed system is applied to a real training program of the university's training center to examine the applicability and feasibility, and the results are analyzed and discussed.